2005
DOI: 10.1186/1471-244x-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Exposure Therapy as a treatment for child war survivors with posttraumatic stress disorder: Two case reports and a pilot study in an African refugee settlement

Abstract: Background: Little data exists on the effectiveness of psychological interventions for children with posttraumatic stress disorder (PTSD) that has resulted from exposure to war or conflictrelated violence, especially in non-industrialized countries. We created and evaluated the efficacy of KIDNET, a child-friendly version of Narrative Exposure Therapy (NET), as a short-term treatment for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
117
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 43 publications
0
117
0
5
Order By: Relevance
“…Similar to conventional exposure therapy, NET aims to reduce PTSD symptoms by confronting the patient with the memories of the traumatic event (Onyut et al, 2005). The focus of NET is to integrate the typically fragmented, gap-fi lled reports of traumatic experiences into a coherent narrative and to bring about the habituation of emotional responses to reminders of the traumatic event (Bichescu, Neuner, Schauer, & Elbert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to conventional exposure therapy, NET aims to reduce PTSD symptoms by confronting the patient with the memories of the traumatic event (Onyut et al, 2005). The focus of NET is to integrate the typically fragmented, gap-fi lled reports of traumatic experiences into a coherent narrative and to bring about the habituation of emotional responses to reminders of the traumatic event (Bichescu, Neuner, Schauer, & Elbert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen of 20 pre-post effect sizes for PTSD were significant, ranging from small (SMC = 0.29, Lange-Nielsen et al, 2012) to large (SMC = 1.94, Onyut et al, 2005). Eight of the significant effects were achieved using CBT techniques, two in a meditation-relaxation condition (Catani et al, 2009; Schauer, 2008), one with a general education programme (Gupta & Zimmer, 2008), one with EMDR combined with psychodynamic therapy (Oras et al, 2004), one with a writing intervention (Lange-Nielsen et al, 2012), and a multilevel treatment particularly oriented to the needs of young refugees (Ellis et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…O’Shea and colleagues did not report the reasons for the high attrition. Two studies reported intent-to-treat analyses (Betancourt et al, 2012a; Onyut et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations